Optimal scheduling of the combined power and desalination system - Shengnan Xiao; Qingzheng Guan; Weitao Zhang; Lianying Wu (Energy Reports, 2022)
In this paper, the scheduling model is proposed that addresses the operational optimization of the combined power and desalination (CPD)system, which is described as a mixed integer non-linear programming (MINLP) problem with the maximizing total economic benefits and the time-dependent electricity price is considered. The typical day of each season is selected as one scheduling cycle. The results showed: The multi-stage flash (MSF) system keeps running in the total scheduling cycle and the water production rate varies between 2,000 t/h and 4,000 t/h. The reverse osmosis (RO) system only keeps running in the Spring. In the other seasons, a part group’s module of RO system would be shutdown following the increasing demand of electricity. The higher electricity price, the more electricity is supplied to the users and the less water is produced. Vice versa, less electricity and more water are produced. On stand-alone operation mode, the largest fluctuation range of electricity varies from 360 to 510 MW in Summer. The least range varies from 270 to 330 MW in Spring. On the scheduling mode, the difference of the largest and least value varies between 10 to 20 MW. The operation stability and efficiency will be improved by the optimal scheduling of the CPD system.